Interactions between exogenous FGF-2 and sulfonic groups: in situ characterization and impact on the morphology of human adipose-derived stem cells - Amorim, Sara (2013)
FGF-2 is often used as a supplement to stem cells culture medium aiming at preserving their self-renewal capacity and plasticity through the passages. However, little is known on the influence of the underlying substrate in these interactions. In this study, we have used mixed self-assembled monolayers with different ratios of −SO3H and −OH tail groups to investigate the influence of substrate properties (e.g., charge) on the FGF-2 adsorption and activity. QCM-D data demonstrated that, in the presence of −OH groups, the quantity of the adsorbed FGF-2 is proportional to the percentage of surface −SO3H groups. The bioactivity of the adsorbed FGF-2 follows the same tendency as demonstrated by its interactions with anti-FGF-2. Surprisingly, the adlayer of FGF-2 formed on the surface containing only SO3H-tailed SAMs was similar to the surface with 25% of −SO3H groups, demonstrating that FGF-2 adsorption is not solely driven by electrostatic interactions. We related these results with changes in the morphology of adipose-derived stem cells (ASCs) cultured on the same surfaces.